2023
DOI: 10.37080/nmj.137
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis Of Depth of Curve Of Spee Between Individuals with Normal Dentition And Individuals With Occlusally Worn Out Dentition

Abstract: The World Health Organization has declared the novel coronavirus (SARS-CoV-2) Covid-19 as a pandemic as it has spread globally. Understanding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) global dispersal pattern, it is important to know the environmental parameters within which the virus survives. There is adequate evidence in epidemiological and biological aspects to prove human beings are prone to viral pathogens such as Middle East respiratory syndrome coronavirus, respiratory syncytial viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It now plays a critical role in developing essential skills of life and the provision of learning opportunities for home-schooled teens. This type of learning presents a more significant challenge for physical education and sports teachers ( Dhakal & Pd. Pokhrel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It now plays a critical role in developing essential skills of life and the provision of learning opportunities for home-schooled teens. This type of learning presents a more significant challenge for physical education and sports teachers ( Dhakal & Pd. Pokhrel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…5). Other than biological aspects, the higher number of confirmed cases recorded in colder environments was due to the human body secreting less lymphoproliferative hormone, leading to decreased immunogenicity effects and increased risk of infection [24]. Consequently, the virus could attack and rapidly infect humans during the period [1,54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies are investigating the association between environmental factors (temperature and humidity) and the viability, transmission, and survival of the coronavirus [23][24][25][26]. The results primarily demonstrated that temperature was more significantly associated with the transmission of COVID-19 [27][28][29] and its survival period on the surfaces of objects [30].…”
Section: Transmission and Symptoms Of Covid-19mentioning
confidence: 99%